Industrial Engineering in the Big Data Era Selected Papers from the Global Joint Conference on Industrial Engineering and Its Application Areas, GJCIE 2018, June 21-22, 2018, Nevsehir, Turkey - Calisir, Fethi; Cevikcan, Emre.; Camgoz Akdag, Hatice; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book gathers extended versions of the best papers presented at the Global Joint Conference on Industrial Engineering and Its Application Areas (GJCIE), held in Nevsehir, Turkey, on June 21-22, 2018. They reports on industrial engineering methods and applications, with a special focus on the advantages and challenges posed by Big data in this field. The book covers a wide range of topics, including decision making, optimization, supply chain management and quality control.
Part I Industrial Engineering -- Part II Engineering and Technology Management -- Part III Healthcare Systems Engineering and Management.
Keywords: Industrial Management; Application software; Production management; Industrial Management; Computer and Information Systems Applications; Operations Management